Рідкісні лісові угруповання Кременецьких Гір - Melnik, V.I.; Parubok, M.I.; Glinska, S.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of investigation of rare, included in Green Book of Ukraine, of beech durmast oak forests in Kremenetzky Mountains (Ternopil region) are considered. Recommendations for improvement of conservation of the floristic diversity of Krementzky Mountains are proposed.